Formal modeling: actors, open systems, biological systems essays dedicated to Carolyn Talcott on the occasion of her 70th Birthday - Agha, Gul.; Danvy, Olivier; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This Festschrift volume, published in honor of Carolyn Talcott on the occasion of her 70th birthday, contains a collection of papers presented at a symposium held in Menlo Park, California, USA, in November 2011. Carolyn Talcott is a leading researcher and mentor of international renown among computer scientists. She has made key contributions to a number of areas of computer science including: semantics and verification of progamming languages; foundations of actor-based systems; middleware, meta-architectures, and systems; Maude and rewriting logic; and computational biology. The 21 papers presented are organized in topical sections named: Essays on Carolyn Talcott; actors and programming languages; cyberphysical systems; middleware and meta-architectures; formal methods and reasoning tools; and computational biology.
Two PhD Students for the Price of One -- Honoring Carolyn Talcott's Contributions to Science -- Ten Years of Analyzing Actors: Rebeca Experience -- Mathematical Models of Object-Based Distributed Systems -- From Explicit to Symbolic Types for Communication Protocols in CCS -- Abstract LR-Parsing -- Fractionated Software for Networked Cyber-Physical Systems: Research Directions and Long-Term Vision -- Model Feasible Interactions in Distributed Real-Time Systems -- Puff, The Magic Protocol -- A Formal Methodology for Compositional Cross-Layer Optimization -- From Service Identification to Service Selection: An Interleaved Perspective -- Towards a System Model for Ensembles -- Algorithmic Aspects of Risk Management -- Parameterized Metareasoning in Membership Equational Logic -- Fast Sort Computations for Order-Sorted Matching and Unification -- Solving the First Verified Software Competition Problems Using PVS -- Towards a Maude Formal Environment -- Multisimulations: Towards Next Generation Integrated Simulation Environments -- Semantics, Simulation, and Formal Analysis of Modeling Languages for Embedded Systems in Real-Time Maude -- Computational Biology: A Programming Perspective -- Applications of Pathway Logic Modeling to Target Identification.
Electronic reproduction.
Keywords: Formal methods (Computer science); Computer software -- Verification; Electronic books